Implementasi Kegiatan Kepramukaan di Sekolah Dasar: Analisis Kualitatif terhadap Dampaknya pada Pengembangan Soft Skills Siswa - Andini Dita Maharani (Jurnal Pena Karakter : Jurnal Pendidikan Anak dan Karakter, 2024)
Scouting programs in elementary schools play an important role in developing students' character and soft skills, including communication, cooperation, leadership, and responsibility. This study analyzed the impact of scouting activities on students' soft skills using a descriptive qualitative approach, involving two students and one teacher. Data were obtained through interviews and observations. The results showed an increase in communication skills (87.5%), cooperation (80%), and responsibility (95%). Students were active in activities such as team games and received positive responses from teachers, who noted increased discipline and cooperation. Limitations of the study include the small sample size and short observations. Further research is expected to expand the sample and duration of observations to understand the long-term impact. In conclusion, scouting is effective in improving soft skills and requires support from schools and parents to optimize student development.